The Response of Growth and Y ield of the Semi-dwarf Wheat Cultivar ‘Sidi Misri 1’ to Water Regime and Cycocel. - EL-SHARKAWY, M. A.; SOROUR, F. A.; SHAALAN, M. I.; SGAIER, K. (The Libyan Journal of Agriculture, 2023)
The response of growth and yield of the semi-dwarf wheat cultivar ‘Sidi Misri I’, Triticum aestivum L, to water regime and Cycocel (CCC) application was investigated during the 1973/1974 and 1974/1975 growing seasons at the Faculty of Agriculture Farm in Tripoli. In general, there were significant increases with supplementary irrigation in plant height, peduncle length, spike length, number of tillers per plant, number of spikes per plant, total yield, grain yield, straw yield, harvest index, grain weight per plant, grain weight per spike, number of grains per plant, number of grains per spike, number of grains per square meter, and the weight of 1,000-grains. The magnitude of these increases in yield and yield components due to irrigation was greatly enhanced by the addition of stable manure to the soil before planting. In addition to supplementary irrigation and stable manure, the CCC application at the4-leaf stage produced the highest grain yield of 5.969 tons/ha. The response of the various traits studied in this investigation to CCC treatments were variable.